2012
DOI: 10.1504/ijnt.2012.049463
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the photocatalytic activity of ZnO nanoparticles for UV protection applications

Abstract: The detrimental effects of UV radiation are having a significant impact on our life and environment. The development of effective UV shielding agents is therefore of great importance to our society. ZnO nanoparticles are considered to be one of the most effective UV blocking agents. However, the development of ZnO-based UV shielding products is currently hindered due to the adverse effects of the inherent photocatalytic activity exhibited by ZnO. This paper reports our recent study on the possibility of reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 59 publications
(65 reference statements)
0
32
0
Order By: Relevance
“…28 Tsuzuki studied the photoactivity of ZnO nanoparticles via impurity doping, and reported that ZnO is a safe UV-blocking agent for several applications. 29 In other similar studies, a multilayer ZnO film was deposited on cotton, providing a UPF of ~12. In order to increase UPF value, copolymer/ZnO has been coated on cotton textiles.…”
Section: Introductionmentioning
confidence: 98%
“…28 Tsuzuki studied the photoactivity of ZnO nanoparticles via impurity doping, and reported that ZnO is a safe UV-blocking agent for several applications. 29 In other similar studies, a multilayer ZnO film was deposited on cotton, providing a UPF of ~12. In order to increase UPF value, copolymer/ZnO has been coated on cotton textiles.…”
Section: Introductionmentioning
confidence: 98%
“…For example doping of ZnO with transition metals modified the band gap energy and influenced the photocatalytic capacity of the respective nanoparticles (Doutt et al, 2009;Peng and Wang, 2010;Tsuzuki et al, 2012). ZnO can be obtained by different methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…74 Manganese was found to increase the photocatalytic activity, 189 but cobalt significantly reduced the production rate of radicals. 190,191 A drawback of this method is the change of color in the nanoparticles, as the defects cause the absorption of visible light.…”
Section: Strategies For the Reduction Of Photocatalytic Activitymentioning
confidence: 99%